2011
DOI: 10.1002/etc.673
|View full text |Cite
|
Sign up to set email alerts
|

Review of the reproductive biology of amphipods and their endocrine regulation: Identification of mechanistic pathways for reproductive toxicants

Abstract: Abstract-The reproductive biology of amphipods is reviewed to update the knowledge of the male and female reproductive processes of oogenesis and spermatogenesis as well as the endocrine systems of amphipods with the aim of advancing studies of reproductive toxicology. The ovarian and reproduction cycles of female gammaridean amphipods are closely correlated with the molt cycle, which is under direct control by the steroid hormone 20-hydroxyecdysone. The ability of males to copulate and subsequently for female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 135 publications
2
58
0
1
Order By: Relevance
“…Indeed, it was established that the molt cycle of M. rosenbergii lasts an average of 15 days (Ross, 2001). Moreover, several studies have highlighted the variation of the 20-HE concentration during the different stages of the molt cycle of crustaceans (Hyne, 2011;Okumura and Aida, 2000;Zou and Bonvillain, 2004;Zou, 2005). The variation of 20-HE concentration observed here could be due to variations of ecdysteroid synthesis according to the developmental stage of prawns.…”
Section: Chlordecone Effects On the 20-he Concentrationmentioning
confidence: 52%
See 4 more Smart Citations
“…Indeed, it was established that the molt cycle of M. rosenbergii lasts an average of 15 days (Ross, 2001). Moreover, several studies have highlighted the variation of the 20-HE concentration during the different stages of the molt cycle of crustaceans (Hyne, 2011;Okumura and Aida, 2000;Zou and Bonvillain, 2004;Zou, 2005). The variation of 20-HE concentration observed here could be due to variations of ecdysteroid synthesis according to the developmental stage of prawns.…”
Section: Chlordecone Effects On the 20-he Concentrationmentioning
confidence: 52%
“…The 20-HE decrease observed here could also be explained by a modification of the excretion rate of the hormone or an inactivation of the enzyme involved in the ecdysteroid biotransformation. Because of the fact that CLD impacts the 20-HE concentration, it could therefore in the long-term disturb the molting of organisms which is induced by this hormone (Hyne, 2011;Rodríguez et al, 2007). This hypothesis is supported by the studies of Hirano et al (2009) which have shown that low 20-HE concentration in the shrimp Americamysis bahia exposed to nonylphenol (also known to be an inhibitor of ecdysteroid activity) affected the growth of organisms.…”
Section: Chlordecone Effects On the 20-he Concentrationmentioning
confidence: 89%
See 3 more Smart Citations